2011
DOI: 10.1002/prot.23068
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein interactions: Analysis of a false positive GST pulldown result

Abstract: One of the most common ways to demonstrate a direct protein-protein interaction in vitro is the glutathione-S-transferse (GST)-pulldown. Here we report the detailed characterization of a putative interaction between two transcription factor proteins, GATA-1 and Krüppel-like factor 3 (KLF3/BKLF) that show robust interactions in GST-pulldown experiments. Attempts to map the interaction interface of GATA-1 on KLF3 using a mutagenic screening approach did not yield a contiguous binding face on KLF3, suggesting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The results from both GST pull-down (Fig 6 F) and co-IP experiments (Fig 6 G) revealed that PRR14-2 peptide, which contains the proline rich domain, binds specifically to GRB2. The binding of C-terminal of PRR14 (PRR14-4) to GRB2 was also detected in GST pull-down but not in Co-IP experiment, suggesting a non-specific binding in GST pull-down analysis 37 . Immunofluorescence staining showed the possibility of the 2 proteins interacting with each other spatially and temporally (S2 B).…”
Section: Resultsmentioning
confidence: 96%
“…The results from both GST pull-down (Fig 6 F) and co-IP experiments (Fig 6 G) revealed that PRR14-2 peptide, which contains the proline rich domain, binds specifically to GRB2. The binding of C-terminal of PRR14 (PRR14-4) to GRB2 was also detected in GST pull-down but not in Co-IP experiment, suggesting a non-specific binding in GST pull-down analysis 37 . Immunofluorescence staining showed the possibility of the 2 proteins interacting with each other spatially and temporally (S2 B).…”
Section: Resultsmentioning
confidence: 96%
“…However, it is often overlooked that the presence of soluble protein from bacterial expression does not guarantee correct folding. Soluble, partially-folded aggregates often form and can bind non-specifically to other proteins [22]. Affinity tags can also impact folding, leading to non-specific interactions [23].…”
Section: Resultsmentioning
confidence: 99%
“…The Halo-Tag ® and its ligand bind covalently, leading to a strong, irreversible bond [16]. Further, it increases the amount of soluble protein expressed in contrast to other tags [17], as it reduces the formation of inclusion bodies during recombinant protein expression.…”
Section: Introductionmentioning
confidence: 99%